eIF4A supports an oncogenic translation program in pancreatic ductal adenocarcinoma - Karina Chan (Nature Portfolio, 2019)
Metabolic reprogramming is a hallmark of pancreatic ductal adenocarcinoma (PDA). Here, the authors show that in PDA cells redox and central carbon metabolism are driven by an eIF4F dependent translation program, and combined targeting of eIF4A and glutaminase can impact PDA proliferation.